Functional disability in community-dwelling older people and its associated factors: a cross-sectional study of felda schemes in Pahang, Malaysia - Abdul Wahab, Patimah; Abdul Talib, Nurul Afiah; Nik Mohd Hatta, Nik Noor Kaussar; Saidi, Sanisah; Abdul Mulud, Zamzaliza; Abdul Wahab, Muhammad Nubli; Pairoh, Hasanah; Nik Kamiluddin, Nik Nurfathiah Sa’adah (Universiti Putra Malaysia, 2024)
Introduction: Functional disabilities are common in community-dwelling older people, endangering their well-being and ultimately leading to deterioration in health and loss of ability to work. The ageing process and chronic diseases have been found to have a greater impact on physical or mental disabilities. This study examined functional disability in community-dwelling older people and the identified associated factors. Materials and methods: A cross-sectional study of 305 community-dwelling older people was conducted within FELDA schemes in Pahang. To complete the Malay version of the Barthel Index and provide information on socio-demographic and health status, face-to-face interviews were conducted. Multiple linear regression analysis was performed to examine the predictive factors. Results: The average age of participants was 69.61 years (SD = 6.30). Approximately 90.5% of participants had a functional disability. Age (-0.1 [-0.2, -0.1], P < 0.001), BMI (-0.1 [-0.2, -0.0], P = 0.015), number of chronic conditions (-0.5 [-0.7, -0.3], P < 0.001), and renal disease (-2.1 [-3.7, -0.5]), P = 0.010) were significantly associated with functional disability. Meanwhile, stroke (-5.8 [95% CI: -7.2, -4.4], P < 0.001), knee pain (-0.8 [95% CI: -1.4, -0.1], P = 0.016), and vision problems (-1.8 [95% CI: -2.8, -0.8], P = 0.001) were independent predictors, with stroke being the largest contributor. Conclusion: Our results suggested that functional disability among elderly people in Malaysia was very severe and mainly related to chronic diseases. A health promotion program should aim to help older people delay the onset of disability while optimizing their functional autonomy.